The Role of Institutional Ownership as A Moderating Variable in Determining Disclosure of Tax Avoidance (Mining Sector Companies 2018-2022) - Fatimah, Nurul; Nurdin, Fajar (Universitas Katolik Soegijapranata Semarang, 2024)
The research objective is to determine how profitability, capital intensity, company size, and tax avoidance are influenced by institutional ownership. Sample for this research is 34 mining companies registered between 2018 and 2022 on the Indonesian Stock Exchange. Random effect model (REM) is the test model chosen, and panel regression data is tested using the Eviews12 program. The results of the profitability research have a significant positive result on tax avoidance. Capital intensity has no effect on tax avoidance. Meanwhile, business size has a significant effect on tax avoidance in a negative direction. Institutional ownership is unable to moderate profitability and capital intensity to prevent tax avoidance. However, institutional ownership is able to moderate company size on tax avoidance practices.